Training Need of Farmers in Horticultural Crops in Haryana (Indian Journal of Extension Education, 2021)
Value addition in agriculture predominantly offers a means to increase, rejuvenate and stabilize farm income. Value-added agriculture is fundamentally market-driven. It needs trained and skilled manpower to cope with the demand of rapidly changing markets. The present study was conducted in Haryana state and two districts Hisar from southwest and Sonipat from northeast were selected, purposively. From each district, three blocks were selected randomly. Further, three villages were selected from each block making a total of 18 villages. From each village, ten farmers were selected randomly, making a total sample of 180 farmers. It was found that majority of the respondents were interested in taking training of ‘Farm level packaging and storage’, ‘Development of commercial horticultural nursery for fruit trees and vegetables crops’, ‘Processing and value addition’ and ‘Packaging of nursery plants’. DAE (Directorate of Agriculture Extension) should arrange training programmes based on the necessity of the farmers. Otherwise, it will not bring any positive outcome in the crop production systems of Haryana.